2018
DOI: 10.4103/ortho.ijortho_464_17
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Recurrent Multifocal Osteomyelitis - A Case Series from India

Abstract: Background:Chronic recurrent multifocal osteomyelitis (CRMO) is a rare auto-inflammatory disease of the bone. It tends to be multifocal and usually the symptoms tend to run for months and years before diagnosis is usually made. The objective of our study was to understand the clinical presentation and short-term response to treatment of CRMO patients.Materials and Methods:A retrospective analysis of patients diagnosed with CRMO between 2011 and 2016 was done. Case records of these were retrospectively reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
1
13
2
Order By: Relevance
“…The diagnostic delay ranged from 1 to 72 months, suggesting that CNO is still sometimes not well recognized in our country. In term of clinical manifestation, bone pain is still the most frequency symptom, but the fever rate in our study, which up to 44.4%, is more higher than that in other studies [ 17 , 18 , 20 , 22 , 24 ]. This may be related to bone inflammation.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The diagnostic delay ranged from 1 to 72 months, suggesting that CNO is still sometimes not well recognized in our country. In term of clinical manifestation, bone pain is still the most frequency symptom, but the fever rate in our study, which up to 44.4%, is more higher than that in other studies [ 17 , 18 , 20 , 22 , 24 ]. This may be related to bone inflammation.…”
Section: Discussioncontrasting
confidence: 81%
“…Compared with previous reports, the clinical characteristics of our patients were a little different. (details in Table 4 ) [ 8 , 12 , 15 , 17 25 ] The female advantage in China is not such obvious as European countries [ 8 , 12 , 15 , 18 , 22 25 ]. The median age at diagnosis and diagnostic delays were 9.2 years and 10.2 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The peak onset of CNO in studies from Turkey was between 9 and 10.2 years, and a male predominance was observed in 2 studies [12][13][14]. Likewise, two studies from India and Chile reported male predominance [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Açarı et al [14] reported lesion sites; femur (67.9%), tibia (57.1%), and pelvic bones (32.1%). Concha et al [16] observed lesions of 21% in the upper limb, 9% in the lower limb, and 36% in the axial skeleton, and the other studies reported sites of lesions under different titles and groups [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The median age at diagnosis in pediatric patients is 10 years, with most cases reported between 8 and 13 years [ 4 , 5 , 6 , 7 , 8 ]. In European cohorts, females seem more likely to be affected, with a female-to-male ratio of 2:1 [ 5 , 6 , 7 , 8 , 9 , 10 ], while in Latin American and Indian series a male prevalence is reported [ 11 , 12 ]. Diagnostic delay is common in pediatric CNO, with a mean interval of 12 months between symptom onset and diagnosis in most pediatric studies [ 4 , 6 , 8 , 13 ], possibly related to the rareness of the disease, the discrete findings on examination, and the absence of pathognomonic laboratory studies.…”
Section: Incidence and Demographicsmentioning
confidence: 99%